2008
DOI: 10.1152/ajpheart.00537.2008
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Ca2+ homeostasis is associated with atrial fibrillation in the α1D L-type Ca2+ channel KO mouse

Abstract: current (ICa-L) in the mouse supraventricular tissue. However, its functional role in the heart is just emerging. We used the ␣1D gene knockout (KO) mouse to investigate the electrophysiological features, the relative contribution of the ␣ 1D Ca 2ϩ channel to the global ICa-L, the intracellular Ca 2ϩ transient, the Ca 2ϩ handling by the sarcoplasmic reticulum (SR), and the inducibility of atrial fibrillation (AF). In vivo and ex vivo ECG recordings from ␣1D KO mice demonstrated significant sinus bradycardia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 27 publications
2
55
1
1
Order By: Relevance
“…In agreement with this notion, Mancarella et al 15 have shown that knockout of ␣ 1D (another ␣ subunit of atrial L-type Ca 2ϩ channel) alone is sufficient to cause atrial ECG abnormalities and to enhance AF vulnerability in the absence of changes of other currents such as I Na , I Ca-T , I K , I f , and I to . Moreover, atrial tachyarrhythmias cause atrial mechanical dysfunction related to abnormal handling of cellular Ca 2ϩ , which contributes to thrombus formation.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In agreement with this notion, Mancarella et al 15 have shown that knockout of ␣ 1D (another ␣ subunit of atrial L-type Ca 2ϩ channel) alone is sufficient to cause atrial ECG abnormalities and to enhance AF vulnerability in the absence of changes of other currents such as I Na , I Ca-T , I K , I f , and I to . Moreover, atrial tachyarrhythmias cause atrial mechanical dysfunction related to abnormal handling of cellular Ca 2ϩ , which contributes to thrombus formation.…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, it has been shown that ␣ 1D (an ␣ subunit of atrial L-type Ca 2ϩ channel) knockout mice had atrial ECG abnormalities and enhanced AF vulnerability. 15 Although expression deregulation of Ca 2ϩ channel-encoding genes in AF has been documented, the molecular determinants have remained incompletely understood.…”
mentioning
confidence: 99%
“…Thus far, it is unclear to what extent other CACNA1D mutations or polymorphisms contribute risk for hearing disorders or for SAN dysfunction. Despite a normal life span, Ca V 1.3 2/2 mice also appear more vulnerable to ventricular extrasystoles (Matthes et al, 2004) and atrial fibrillation due to reduced L-type currents and impaired intracellular Ca 2+ handling in atrial myocytes (Zhang et al, 2002;Mancarella et al, 2008). c. Neuropsychiatric Disease.…”
Section: +mentioning
confidence: 99%
“…These mutations are likely to reduce greatly or even abolish the function of the encoded gene product. Ca v 1.3 (a1D) is a key regulator of calcium homeostasis, electrical activity, and maintenance of normal rhythm in the heart (Chahine et al 2008;Mancarella et al 2008), and in Cacna1d knockout mice, gene deletion is associated with hypoinsulinaemia, glucose intolerance, and decreased number and size of pancreatic islets (Namkung et al 2001). It is therefore of interest that genome-wide association analysis in humans has shown an association between polymorphism in the Cacna1d gene and type 2 diabetes (Sookoian et al 2009) and suggests that investigation of the functional consequences of Cacna1d mutations in SHR/OlaIpcv would be worthwhile.…”
Section: Functional Significance Of Detected Genomic Variantsmentioning
confidence: 99%